2012
DOI: 10.1111/j.1460-9568.2012.08239.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐induced sensitization to cocaine: actin cytoskeleton remodeling within mesocorticolimbic nuclei

Abstract: This study investigated the consequence of repeated stress on actin cytoskeleton remodeling in the nucleus accumbens (NAc) and prefrontal cortex (Pfc), and the involvement of this remodeling in the expression of stress-induced motor cross-sensitization with cocaine. Wistar rats were restrained daily (2 hours) for 7 days and, three weeks later, their NAc and Pfc were dissected 45 min after acute saline or cocaine (30 mg/kg i.p.). F-actin, actin-binding proteins (ABP) and GluR1 were quantified by western blottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 100 publications
(136 reference statements)
4
35
0
Order By: Relevance
“…If this is the case, other situations that increase accumbens activity may lead to similar increases in spines. For example, stress can increase dendritic spines in the accumbens when animals are subjected to more aggressive stress regimens such as chronic social defeat stress [52], while weaker stress exposure protocols such as chronic restraint have no effect on dendritic spines in the accumbens [9]. Even milder chronic social defeat stress for 3 sessions of 5 min induce more transient thin spines, while 10 sessions of 10 min cause increases in stubby spine density [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If this is the case, other situations that increase accumbens activity may lead to similar increases in spines. For example, stress can increase dendritic spines in the accumbens when animals are subjected to more aggressive stress regimens such as chronic social defeat stress [52], while weaker stress exposure protocols such as chronic restraint have no effect on dendritic spines in the accumbens [9]. Even milder chronic social defeat stress for 3 sessions of 5 min induce more transient thin spines, while 10 sessions of 10 min cause increases in stubby spine density [52].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this initial report, not all researchers observe persistent cocaine-induced spines after late withdrawal times [26]. More recent studies also suggest that cocaine-induced spines can form very early after withdrawal from repeated cocaine injections (30 min to 4 hours) [7,8], and even form after 6 hours – but not 30 min – after a single acute cocaine injection [4,9]…”
Section: Introductionmentioning
confidence: 96%
“…These stressors also increase subsequent amphetamine (Amph) or cocaine-stimulated extracellular DA in the nucleus accumbens (NAc) (Miczek et al 2011; Pacchioni et al 2007; Tidey and Miczek 1996). While greater NAc DA sensitivity after stress is important, other neural mechanisms such as brain-derived neurotropic factor (BDNF), corticotropin-releasing factor type 1 receptor (CRF-R1) (Boyson et al 2011; Miczek et al 2011), and NAc actin cytoskeleton protein (Esparza et al 2012) are also implicated in this temporal connection between stress and abused drugs. Overall, the neural system common to adult stress-induced sensitization to drugs of abuse is the mesocorticolimbic DA system.…”
Section: Adult Stress Cross-sensitization To Drugs Of Abusementioning
confidence: 99%
“…Indeed, in a recent study by Garcia-Keller et al (2013), robust locomotor sensitization induced by an episode of restraint stress was observed in response to a challenge injection of 15, but not 5 or 10 mg/kg cocaine. Moreover, in studies where cross-sensitizing effects have in fact been observed with a challenge dose of 10 mg/kg cocaine (e.g., [17][18][19]), the stress regimens were considerably more stringent than in ones where such effects were not observed (including ours).…”
Section: Introductionmentioning
confidence: 91%